Strategic Gamification in Communication: Enhancing Engagement in Learning and Health Sectors - Toun, Nicodemus R. (Communica : Journal of Communication, 2024)
Gamification has emerged as a powerful approach in enhancing communication strategies across various domains, including education, health, and public advocacy. This narrative review explores how gamification influences engagement, knowledge retention, and behavioral change through communication. A comprehensive literature search was conducted across databases such as Scopus, Web of Science, PubMed, and Google Scholar using Boolean keyword combinations including "gamification," "communication strategies," "engagement," "education," and "persuasion." Relevant studies were selected based on predefined inclusion and exclusion criteria focusing on peer-reviewed articles published in the last ten years. The findings indicate that key gamification elements—such as rewards, feedback, and competition—significantly boost user interaction and motivation. In educational contexts, gamification enhances learning outcomes and retention, especially when culturally adapted. In health communication and public campaigns, gamified systems promote desired behaviors by leveraging persuasive psychological mechanisms. However, systemic barriers such as digital access, institutional policy gaps, and limited facilitator capacity influence implementation success. This review underscores the need for culturally adaptive, technology-supported, and community-centered gamification policies. It calls for future research on ethical design, long-term impacts, and scalable interventions. Gamification, when strategically implemented, holds promise as a catalyst for sustainable engagement and effective communication.